Valence Band Profile in Two-Dimensional Silicon-Oxygen Superlattices Probed by Internal Photoemission. (18th June 2016) - Kolomiiets, N. M.; Afanas'ev, V. V.; Jayachandran, S.; Delabie, A.; Heyns, M.; Stesmans, A.
Abstract : Energy distribution of electron states in two-dimensional superlattices (SLs) of crystalline silicon layers separated by monolayers (MLs) of oxygen atoms is studied using internal photoemission (IPE) spectroscopy. SLs made of 1, 2 or 5 periods of one ML of O in between 25, 15, 7, 3 or ∼1 nm thick Si layers were studied by using IPE from these SLs into 20-nm thick Al2 O3 dielectric deposited on top of the SL. We observed the reduction of direct optical transition intensity in Si-O SLs when decreasing the Si thickness to 1 nm, indicative of the Si electronic structure distortion inside the SLs. The field dependence of IPE spectral threshold indicates the absence of both the change in Si-O SLs VB energy and any additional field-induced band bending across the SLs. Further, electron spin resonance indicates the absence of additional Si dangling bonds in the Si-O SLs within the sensitivity limit of ≈10 11 cm −2 . These findings suggest that Si-O SLs enhance the carrier mobility by breaking the crystal symmetry and tuning the location of the channel to the region where electrons or holes travel without additional scattering.